Cyclodextrins - Core Concepts and New Frontiers 2023
DOI: 10.5772/intechopen.105688
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrins as Bricks for Tuning Polymer Properties

Abstract: Cyclodextrins are natural cyclic oligosaccharides with a cone shape delimiting a hydrophobic cavity. The rims of cyclodextrins can be functionalized in order to improve their properties. Based on this, cyclodextrins can be linked to polymer chains, which further allows the tuning of the polymer properties. This review describes the methods of polymer functionalization with cyclodextrins and highlights the changes in the physicochemical properties of these materials. This chapter is focused on polymers in solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 119 publications
0
1
0
Order By: Relevance
“…The most common host unit attached to a polymer is represented by cyclodextrins (CDs). Functional polymers based on cyclodextrin have been DOI: 10.1002/macp.202200444 designed and studied reported in time highlighting the enhancement of encapsulation and release ability, the improvement of mechanical characteristics, biodegradability, [1][2][3] Alg is an anionic polysaccharide that is generally used in biomedical and pharmaceutical applications due to its biodegradability, nontoxicity, biocompatibility, low immunogenicity, etc. [4][5][6][7] A number of studies reported on the synthesis of Alg modified with cyclodextrin units.…”
Section: Introductionmentioning
confidence: 99%
“…The most common host unit attached to a polymer is represented by cyclodextrins (CDs). Functional polymers based on cyclodextrin have been DOI: 10.1002/macp.202200444 designed and studied reported in time highlighting the enhancement of encapsulation and release ability, the improvement of mechanical characteristics, biodegradability, [1][2][3] Alg is an anionic polysaccharide that is generally used in biomedical and pharmaceutical applications due to its biodegradability, nontoxicity, biocompatibility, low immunogenicity, etc. [4][5][6][7] A number of studies reported on the synthesis of Alg modified with cyclodextrin units.…”
Section: Introductionmentioning
confidence: 99%